Composites of Poly(ethylene glycol) and Hydroxyapatite: Dynamic Mechanical Study of the Modulus of Elasticity under Cryogenic Conditions - Nur Aini Fauziyah; Euis Nurul Hidayah; Primasari Cahya Wardhani; Ayunda W. Permatasari; Amelia P. Wulandari; M. Jawaid (BioResources)
The cryogenic mechanical behavior of polyethylene glycol (PEG) and hydroxyapatite (HAp) composites was studied using Dynamic Mechanical Analysis (DMA). The HAp was synthesized from chicken eggshells via a hydrothermal process, offering a sustainable, bio-derived source of calcium phosphate. The composites were fabricated through a wet mixing technique to ensure uniform distribution of HAp within the PEG matrix. Cryogenic characterization was conducted over a temperature range of minus 100 °C to 50 °C to evaluate the viscoelastic properties of the composites under extreme conditions. The results demonstrated a significant enhancement in the storage modulus (E′), with the 30 wt% PEG-HAp composite achieving a peak value of 1.128 GPa. This improvement is attributed to the effective impregnation and interfacial interaction between the PEG and HAp phases. These findings indicate the potential applicability of PEG/HAp composites in biomedical and cryogenic environments, although further studies are necessary to explore their specific functional roles in targeted applications. The study contributes to the advancement of biocomposite materials by elucidating the effects of cryogenic conditions on mechanical performance and supports the use of sustainable raw materials in composite fabrication.